Laccase production by free and immobilized mycelia of Peniophora cinerea and Trametes versicolor: a comparative study - Silvério, Sara C. (2013)
The production of laccase by immobilized mycelia of Peniophora cinerea and Trametes versicolor was studied. In an initial stage, experimental assays were performed in Erlenmeyer flasks using free and immobilized mycelium, and the performance of the fungal strains to produce the enzyme was compared. Both fungi adhered into the support material (a synthetic fiber), growing not only on the surface but also in the interspaces of the fibers. Immobilization of P. cinerea provided a 35-fold increase in laccase production when compared to the production obtained by using free mycelium. On the other hand, immobilization of T. versicolor caused a decrease in laccase activity. A comparison between the strains revealed that immobilized P. cinerea (3,500 U/L) surpassed the enzyme production by free T. versicolor (800 U/L). When the conditions that gave the best laccase production to each fungus were employed in a stirred tank bioreactor, very low laccase production was observed for both the cases, suggesting that shear stress and mycelia damage caused by the agitation impellers negatively affected the enzyme production.